Insomnia and suicidal ideation and behaviors in former and current U.S. service members: Does depression mediate the relations?. (June 2017) - Allan, Nicholas P.; Conner, Kenneth R.; Pigeon, Wilfred R.; Gros, Daniel F.; Salami, Temilola K.; Stecker, Tracy
Abstract: Insomnia is a risk factor for Suicidal Ideation (SI) and Behavior (SB), yet the nature of the relations is unclear, including the potential mediating role of cognitive and affective/somatic symptoms of depression. It was hypothesized that the impact of insomnia on SI would be mediated through depressive symptoms and that insomnia would directly impact SB. Current and former military service members ( N =405; M age =31.6 years, SD =7.3; 90.4% male, 76.5% White) who endorsed recent suicidal ideation and/or a history of suicide attempt completed measures of insomnia, depression, SI, and SB at baseline and at month 12 follow-up. Mediation models were conducted using structural equation modeling. Significant mediation from insomnia to baseline SI and month 12 SI was found through cognitive/affective depression. Insomnia was directly related to SB occurring between baseline and month 12 follow-up. These findings suggest that cognitive/affective depression mediates the association with SI but not SB. Results build on research showing the importance of depressive symptoms in SI in particular. The direct and indirect pathways from insomnia to SI/SB suggest that clinicians should be aware of these relations when treating patients reporting insomnia. Highlights: Relations between insomnia and Suicidal Ideation/Behavior (SI/SB) were examined. Structural equation models were used to examine concurrent/prospective relations. Cognitive depression symptoms mediated the relation between insomnia and SI. Insomnia was directly related to SB, though not when controlling for depression.